Islam-Malay Identity on Muslim Inside’s Community; A Case Study in Sri Wangi Village, Kapuas Hulu West Kalimantan - Saripaini, Saripaini (The Pontianak State Institute of Islamic Studies, 2018)
The researcher wanted to see how the Malay identity devices were identified as Muslims by the people of the rural areas of West Kalimantan. Data was collected in the village of Sri Wangi, a remote village in West Kalimantan or western Borneo, precisely in Kapuas Hulu District, 15 hours away by public transportation from the city of Pontianak. Data was collected through observations in the field of people's lives and interviews with community leaders and some residents with Malay identities who were lineages not Malays. From the results of the interview, information was obtained that the identity of the community's Malayness was obtained from its Islamic identity. They introduced themselves as Malays and were known to the public as Malays. The Malay language used by the community is very much different from Pontianak Malay. The Malays in Sri Wangi village still carry out what their ancestors did and believe that every ritual that is not carried out has consequences.